Correlation among corporate social responsibility, brand equity and firm performance based on feeling of staff in travel companies in TPP integration - Hoàng Anh Viện (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh, 2020)
The aim of this paper is to identify the relationship between staff Corporate Social Responsibility (CSR) awareness of brand equity and firm performance in the tourism sector using a well-designed questionnaire to collect data from 336 staff working in tourism enterprises. The research uses various models of Cronbach’s Alpha coefficient, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Structural Equation Analysis (SEM) to analyze the data. Research results show that all four factors of staff feelings about economic responsibilities, ethical responsibilities, legal responsibilities and philanthropic responsibilities have a positive impact on brand equity and firm performance. Besides, brand equity has a positive impact on firm performance. The study also suggests some implications for tourism managers to enhance CSR activities in their business.